2022
DOI: 10.5604/01.3001.0015.7103
|View full text |Cite
|
Sign up to set email alerts
|

Is the Structure of Polish Agriculture Changing? A Comparison Based on the Results of Recent General Agricultural Censuses

Abstract: Structural changes in Polish agriculture are necessary. First of all, the scale is expected to increase and, hence, input efficiency. The aim of the research is to determine whether the concentration of resources and production in Polish agriculture is taking place and what is the direction. Data from two general agricultural censuses conducted by the Central Statistical Office in 2010 and 2020 were used. It was determined what main directions of changes were observed in Polish agriculture, as well as whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
2
0
2
Order By: Relevance
“…In groups III and IV, the shares of farms of 5-10 ha and 10-20 ha decreased, while in groups I and II, the shares of those farms increased. Similar conclusions were arrived at by Filipiak and Wicki [53], who indicated that share of farms above 20 ha increased by 7 p.p. between 2010 and 2020.…”
Section: Changes In the Size Structure Of Farms According To Typologi...supporting
confidence: 86%
“…In groups III and IV, the shares of farms of 5-10 ha and 10-20 ha decreased, while in groups I and II, the shares of those farms increased. Similar conclusions were arrived at by Filipiak and Wicki [53], who indicated that share of farms above 20 ha increased by 7 p.p. between 2010 and 2020.…”
Section: Changes In the Size Structure Of Farms According To Typologi...supporting
confidence: 86%
“…Rolnictwo w Polsce charakteryzuje się stosunkowo niską wydajnością (Baer-Nawrocka, 2017;Bereżnicka i Wicki, 2023;Ściubeł, 2021). Wynika to z małej skali produkcji i niskiego tempa wzrostu wydajności czynników wytwórczych, dlatego zmiany strukturalne w polskim rolnictwie są konieczne (Filipiak i Wicki, 2022). Specjalizacja gospodarstw rolnych i związany z nią wzrost skali produkcji w realiach polskiego rozdrobnionego rolnictwa to niewątpliwie kierunek jego rozwoju i możliwość poprawy wyników produkcyjnych i ekonomicznych gospodarstw (Kuś, 2012;Marzec i Pisulewski, 2020;Smędzik, 2010).…”
Section: Przegląd Literaturyunclassified
“…2019). W Polsce obserwuje się stały wzrost koncentracji produkcji w rolnictwie, jest to jednak proces o małej dynamice (Filipiak, Wicki 2022). Część badaczy zauważa mechanizm dywestycji w gospodarstwach rolnych, gdyż wiele gospodarstw mniejszych nie daje wystarczającego dochodu dla utrzymania rolnika i jego rodziny, stąd decyzje o rezygnacji z części zasobów, z prowadzenia produkcji zwierzęcej, a w efekcie niższa produktywność ziemi, kapitału i zwykle pracy (Wojewodzic, Mikołajczyk 2011).…”
Section: Skala Działalności a Wyniki Ekonomiczne I Możliwości Rozwoju...unclassified